Gender and Sexuality Justice in Asia Finding Resolutions through Conflicts - Goh, Joseph N.; Bong, Sharon A.; Kananatu, Thaatchaayini (Springer Nature Singapore : Imprint: Springer, 2020)
XXX, 227 p. 1 illus.